Exome Sequencing of a Portuguese Cohort of Frontotemporal Dementia Patients: Looking Into the ALS-FTD Continuum - Tábuas-Pereira, Miguel; Santana, Isabel; Gibbons, Elizabeth; Paquette, Kimberly; Almeida, Maria Rosário; Baldeiras, Inês; Bras, Jose; Guerreiro, Rita (Frontiers in Neurology, 2022)
Introduction: Frontotemporal dementia (FTD) is considered to be part of a continuum with amyotrophic lateral sclerosis (ALS). Many genes are associated with both ALS and FTD. Yet, many genes associated with ALS have not been shown to cause FTD. We aimed to study a Portuguese cohort of FTD patients, searching for variants in genes associated with both FTD and/or ALS. Methods: We included 57 thoroughly characterized index FTD patients from our memory clinic, who were not carriers of pathogenic variants in GRN, MAPT or C9orf72. We performed exome sequencing and 1) prioritized potential FTD and ALS causing variants by using Exomiser to annotate and filter results; and 2) looked specifically at rare variability in genes associated with FTD (excluding GRN, MAPT and C9ORF72) and/or ALS. Results: We identified 13 rare missense variants in 10 patients (three patients had two variants) in the following genes: FUS, OPTN, CCNF, DCTN1, TREM2, ERBB4, ANG, CHRNA4, CHRNB4 and SETX. We found an additional frameshift variant on GLT8D1 in one patient. One variant (ERBB4 p.Arg1112His) gathers enough evidence to be classified as likely pathogenic by the ACMG criteria. Discussion: We report, for the first time, an expanded study of genes known to cause FTD-ALS, in the Portuguese population. Potentially pathogenic variants in ERBB4, FUS, SETX, ANG, CHRNA4 and CHRNB4 were identified in FTD patients. These findings provide additional evidence for the potential role of rare variability in ALS-associated genes in FTD, expanding the genetic spectrum between the two diseases.